Propeller clock / Nur Amalina Zulkifli & Nurasyikin Ishak - Zulkifli, Nur Amalina; Ishak, Nurasyikin (2015)
The propeller clock is an electronic devices which has a series of LEDs on board that rotate with the help of a motor to give an illusion of a watching a clock (Digital or Analogue). This requires a DC motor which rotates the PCB connected to it with sufficient speed so as to create the illusion. The LEDs are connected to a microprocessor PIC16C84 or 16F84 which is so programmed to switch ON and OFF the LEDs in sequence and with a time delay to approximately match with the rotating speed of the motor. One of the phases of the DC motor is directly feedback to the microprocessor to identify the position of the motor at any instant. The important components for this project is DC motor, PIC16F84 and others. Troubleshooting must be carried out when the circuits were not functioning as expected. The circuits have to be troubleshoot to define the location of the fault occurs. Unsuitable component. In the PROTEUS library, there are too many components from the same type and there are look alike. However, the datasheet or characteristics is not the same and not compatible with this circuit. Some devices are active while others are not active. In order to make sure that the simulation is success, try and test methods are used until the desired result is achieved. It so hard when to convert to Gerber file. The project must be rearrange back the position of components to ensure the best position of the device . The circuit should be more simple then the people can use this device for event and at home. Decide to add some buzzer to make some sound. This project must change motor or CPU fan that can not make some noise when it rotates.